TRADISI BALIMAU KASAI DESA TANJUNG BERULAK KECAMATAN KAMPAR - Rian Hidayat; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research was conducted in Tanjung Berulak Village, Kampar District. The purpose of this research is to find out the social, cultural and economic meaning of the Balimau Kasai tradition. This study uses a descriptive qualitative research method. Data collection was carried out using in-depth interview techniques and documentation. The results of the study show that the Balimau Kasai Tradition is a special event for the people of Tanjung Berulak Village where the community interprets the Balimau Kasai bath as a symbol of purification and cleansing before entering the holy month of Ramadan. In the Balimau Kasai tradition there is social value, namely the existence of well-established communication or community interaction. The Balimau Kasai tradition is packaged very lively by presenting various attractions such as traditional calempong music, single organ music and folk games that the public can watch. In the Balimau Kasai Tradition, there is economic value, namely when the Balimau Kasai tradition event is held, some people use it to open a business such as selling food, drinks and a place to park in the area where the Balimau Kasai Tradition event is held. Keywords: Meaning, Balimau Kasai Tradition, Tanjung Berulak Village